Implementation Of The Importance Performance Analysis (Ipa) Method In Measuring The Level Of Community Satisfaction With Services At The Kelurahan Office Padang Jati Web-Based Village Office - Haluan Saputra Andalah; Herlina Latipa Sari; Prahasti Prahasti (Penerbit Jurnal Indonesia, 2023)
The purpose of this research is to implement the Importance Performance Analysis (IPA) method and create a web-based application in measuring the level of community satisfaction with the services provided by the Padang Jati Village Office. The web-based application for measuring the level of community satisfaction with services at the Padang Jati Urban Village Office was created using the PHP programming language and MySQL database which can be accessed online via the domain url link http://haluan.online. Based on the tests that have been carried out, it is found that this application is very helpful in managing and evaluating data on community satisfaction assessment of services at the Padang Jati Urban Village Office so that the level of community satisfaction is known and this application can be used as a forum for the community to provide an assessment of community satisfaction with services at the Padang Jati Urban Village Office.